Audio–visual crossmodal correspondences in domestic dogs (Canis familiaris). (13th November 2019) - Korzeniowska, A. T.; Root-Gutteridge, H.; Simner, J.; Reby, D.
Abstract : Crossmodal correspondences are intuitively held relationships between non-redundant features of a stimulus, such as auditory pitch and visual illumination. While a number of correspondences have been identified in humans to date (e.g. high pitch is intuitively felt to be luminant, angular and elevated in space), their evolutionary and developmental origins remain unclear. Here, we investigated the existence of audio–visual crossmodal correspondences in domestic dogs, and specifically, the known human correspondence in which high auditory pitch is associated with elevated spatial position. In an audio–visual attention task, we found that dogs engaged more with audio–visual stimuli that were congruent with human intuitions (high auditory pitch paired with a spatially elevated visual stimulus) compared to incongruent (low pitch paired with elevated visual stimulus). This result suggests that crossmodal correspondences are not a uniquely human or primate phenomenon and they cannot easily be dismissed as merely lexical conventions (i.e. matching 'high' pitch with 'high' elevation).